Analisis Kebutuhan Ideal Tenaga Rekam Medis pada Unit Filling - Rizal Pratama Adi Putra; Syamsuriansyah Syamsuriansyah; Uswatun Hasanah; Musparlin Halid; Ikhwan Ikhwan (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2023)
The availability of adequate Human Resources (HR) in accordance with the scientific field is the main focus of various units in the Mataram City Hospital, especially medical recorders. This study aimed to determine the ideal number of medical recorder personnel needed in the filing unit. This type of research uses a quantitative approach in Mataram City Hospital with a sample of 4 people. Calculate ideal medical recorder staffing needs using the Workload Indicator Staffing Need (WISN) method. The results show that the workload is still relatively high. The number of personnel working at this time is still lacking. The number of medical recorders does not match the workload. The staff should be 7 people, while the current staff is 4 people, so they still need 3 more people. The need for medical recorders is not ideal and the hospital still needs additional medical recorders in the filling unit.